An extension of case-based decision theory by using Dempster–Shafer theory of evidence. (12th February 2018) - Du, Fei; Liu, Feiyan
Abstract : Purpose: This study aims to propose a new decision-making method by integrating case-based decision theory and the Dempster–Shafer theory of evidence. Design/methodology/approach: The study developed the entire computational procedures for the proposed method and used a numerical example to illustrate its method. Findings: The results show that not only the own experiences of the decision-maker but also the opinions of other persons contribute to the selection. Case-based decision theory provides a fundamental technique for the decision-making procedure, and the Dempster–Shafer theory of evidence offers support to deal with the different sources of decision information. Research limitations/implications: In case-based decision theory, the utility is a subjective concept, which cannot be measured easily in numbers. Thus, future research should seek a new method to replace the utility. In addition, how to assess the importance of different persons' experiences and opinions is an important component of this method. Originality/value: The contributions of the paper are mainly reflected in three aspects. The first is to expand the traditional concept of "case" of case-based decision theory to multiple sources of cases, which include not only the decision-maker's own experiences but also other persons' opinions. The second is to provide a decision-making framework by integrating case-based decision theory and the Dempster–Shafer theory of evidence. The third is to develop the entire computational procedures for the proposed method.